Science Teachers’ Lived Experiences and Challenges during COVID-19 Pandemic - Pandoy, Lordjan Kenneth L.; Diaz, Zea Oryza May H.; Salem, Kristine Jane G.; Damaso, Junalen M.; Cabaylo, Rey M.; Abo, Christine P. (Indonesian Journal of Teaching in Science, 2022)
COVID-19 pandemic has negatively affected all areas of lifestyle, especially the education sector, from both the students' and teachers' points of view. As we are all concerned with students' difficulties, this study focuses on teachers' lived experiences and challenges and their adaptive strategies in class operations, especially in teaching Science Education. This study is interview-based data instrumentation as it is a phenomenological type of research exploring the lived experiences of Science teachers. Lived experiences, challenges, and adaptive strategies are the thematic base of the data. Findings revealed that (1) there are three core themes under the lived experiences of Science teachers, including building relations, call of duty, and instruction reconstruction. (2) Science teachers were also mostly challenged during distance learning during the COVID-19 pandemic, including the authenticity of students' outputs, instruction delivery, internet connectivity, lack of resources, safety, and topography, which resulted in the difficulty of Science class operation. Despite the lived experiences and challenges brought by distance learning, (3) they learned to possess adaptability, accept assistance, be flexible and innovative, manage time, and use a specialized strategy or radio-based instructions. The study recommends that Science teachers exert extra effort, be resourceful, and cope with digital divides such as attending seminars and workshops to better utilize opportunities in distance learning. They must possess a positive outlook in every way possible. The higher office of the education sector initiates adaptive strategies for teachers.